Chromatin remodeling analysis reveals the RdDM pathway responds to low-phosphorus stress in maize - Luo, Bowen; Zhang, Ziqi; Li, Binyang; Zhang, Haiying; Ma, Junchi; Li, Jing; Han, Zheng; Zhang, Chong; Zhang, Shuhao; Yu, Ting; Zhang, Guidi; Ma, Peng; et al. (Wiley, 2024)
Chromatin in eukaryotes folds into a complex three-dimensional (3D) structure that is essential for controlling gene expression and cellular function and is dynamically regulated in biological processes. Studies on plant phosphorus signaling have concentrated on single genes and gene interactions. It is critical to expand the existing signaling pathway in terms of its 3D structure. In this study, low-Pi treatment led to greater chromatin volume. Furthermore, low-Pi stress increased the insulation score and the number of TAD-like domains, but the effects on the A/B compartment were not obvious. The methylation levels of target sites (hereafter as RdDM levels) peaked at specific TAD-like boundaries, whereas RdDM peak levels at conserved TAD-like boundaries shifted and decreased sharply. The distribution pattern of RdDM sites originating from the Helitron transposons matched that of genome-wide RdDM sites near TAD-like boundaries. RdDM pathway genes were upregulated in the middle or early stages and downregulated in the later stages under low-Pi conditions. The RdDM pathway mutant ddm1a showed increased tolerance to low-Pi stress, with shortened and thickened roots contributing to higher Pi uptake from the shallow soil layer. ChIP-seq results revealed that ZmDDM1A could bind to Pi- and root development-related genes. Strong associations were found between interacting genes in significantly different chromatin-interaction regions and root traits. These findings not only expand the mechanisms by which plants respond to low-Pi stress through the RdDM pathway but also offer a crucial framework for the analysis of biological issues using 3D genomics.